HUBUNGAN PENGETAHUAN DENGAN UPAYA PENCEGAHAN DINI OSTEOPOROSIS WANITA USIA 45-60 TAHUN - Situmorang, Pretty; Manurung, Melva (Jurnal Keperawatan Priority, 2020)
International Osteoporosis Foundation (IOF) revealed that 1 in 4 women in Indonesia with an age of 50-80 years have a risk of osteoporosis. Loss of the hormone estrogen after menopause increases risk of developing osteoporosis. This research aims to reveal the Relationship between Knowledge and Early Prevention of Osteoporosis in Women 45-60 Years Old in Banua Huta Village, Sigumpar District, Toba Samosir Regency in 2020. This study used a descriptive approach with a sample of 35 people used total sampling. This study uses the Spearman correlation test. The results of the study are related to knowledge with early prevention of osteoporosis Women aged 45-60 years in Banua Huta Village, both variables with a sig. (2-tailed) value of 0.003 with a very strong relationship strength r = 0.09. This happens because people's perceptions about the concept of healthy pain that are not in line even very contrary to the health service provider, the community consider illness is a state of the body lying in bed and can not do any activities so prevention efforts are ignored because health problems are not a priority in life and life and there are still many factors that influence a person to take any action not just knowledge. Health workers in Puskesmas have the role of providing information in the form of counseling or health education to elderly women about knowledge and efforts to prevent early osteoporosis so that the number of osteoporosis does not increase.